Electrical characteristics of gallium nitride and silicon based metal-oxide-semiconductor (MOS) capacitors - Hossain, Md Tashfin Zayed (Kansas State University, 2013)
The integration of high-κ dielectrics with silicon and III-V semiconductors is important due to the need for high speed and high power electronic devices. The purpose of this research was to find the best conditions for fabricating high-κ dielectrics (oxides) on GaN or Si. In particular high-κ oxides can sustain the high breakdown electric field of GaN and utilize the excellent properties of GaN. This research developed an understanding of how process conditions impact the properties of high-κ dielectric on Si and GaN. Thermal and plasma-assisted atomic layer deposition (ALD) was employed to deposit TiO₂ on Si and Al₂O₃ on polar (c-plane) GaN at optimized temperatures of 200°C and 280°C respectively. The semiconductor surface treatment before ALD and the deposition temperature have a strong impact on the dielectric’s electrical properties, surface morphology, stoichiometry, and impurity concentration. Of several etches considered, cleaning the GaN with a piranha etch produced Al₂O₃/GaN MOS capacitors with the best electrical characteristics. The benefits of growing a native oxide of GaN by dry thermal oxidation before depositing the high-κ dielectric was also investigated; oxidizing at 850°C for 30 minutes resulted in the best dielectric-semiconductor interface quality. Interest in nonpolar (m-plane) GaN (due to its lack of strong polarization field) motivated an investigation into the temperature behavior of Al₂O₃/m-plane GaN MOS capacitors. Nonpolar GaN MOS capacitors exhibited a stable flatband voltage across the measured temperature range and demonstrated temperature-stable operation.
Keywords: MOS capacitor; GaN; High-k dielectric; Electrical characterization; Atomic layer deposition; Interface trap density; Chemical Engineering (0542); Materials Science (0794)